Introduction - Sanfelippo, Luis César (2024)
In recent years, the term “trauma” has become one of the keywords of Western culture. When a person or a group goes through an experience that seems to shatter the foundations of their lives, its use seems to impose itself as if it were a pristine and self-evident idea. Subjectivities constructed around a past event that continues in the present, or peoples that today experience the present consequences (all too present) of past sufferings; in both spheres, the notion of trauma is called upon to explain a particular alteration of memory and mental functioning, becoming one of the categories derived from “psy” discourses most embraced by contemporary thought.